Comparing HZETRN, SHIELD, FLUKA and GEANT transport codes. (August 2017) - Norbury, John W.; Slaba, Tony C.; Sobolevsky, Nikolai; Reddell, Brandon
Abstract: For the first time, the American (NASA) and Russian (ROSCOSMOS) space radiation transport codes, HZETRN and SHIELD respectively, are directly compared to each other. Calculations are presented for Galactic Cosmic Ray (GCR) minimum Hydrogen, Oxygen and Iron projectiles incident on a uniform Aluminum cylinder of varying thickness. Comparisons are made for the flux spectra of neutrons, light ions (Z≤ 2), heavy ions (Z> 2) and pions emitted from the back of the Aluminum cylinder. In order to provide more benchmark comparisons, some calculations with the GEANT and FLUKA transport codes are also shown.